(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The main environmental problems generated by companies in the textile, apparel and footwear chains are related to the pollution of soil, air, water, inadequate disposal of solid and liquid waste that cause impacts on the environment and are harmful to the health of the population. Thus, the main objective of this article is to evaluate the technical feasibility of manufacturing seamless fabric, made in knitting machines, using as raw materials fibers from woven, knits and non-woven fabrics discarded from the textile industries in the city of Ibitinga (São Paulo, Brazil). Parts from fabrics, knits and non-woven fabrics were selected, with 100% polyester composition. The textiles were cut in an automatic cutter and shredded in a shredder. The shredded fibers from the textiles were mixed with recycled polyester fibers (PET), using the proportion of 50% shredded fibers and 50% recycled polyester (PET), the fibers were spun in a ring spinning and then transformed into knitted fabrics. The articles produced show that there is feasibility for the fabrication of seamless knitted uppers using the circular economy model.